Analisis Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perbankan Syariah - Achmadani, Fadhlika Sugeng; , Dr. Rini Kuswati, S.E., M.Si (2015)
This study describes the relationship between good corporate governance with financial performance on banking syariah companies. The indicators used of explain good corporate governance in this study consisted of the size of the board of directors, proportions of independent commissioners, and the number and size of the company's audit committee.The method of analysis used in this study multiple regression, because in accordance with a purpose of this study was to analysis the influence of independent variable on the dependen variables. Sample used in this study were all banking syariah companies listed to Jakarta Islamic Index (JII) in the period 2011-2014. To determine the selection of the sample used purposive sampling method. By using the method the companies are obtained 10 banking syariah companies that will be serve as sample in this study.From the result of hypothesis testing in this study, it show that the size of the board of direstors not influential significant toward financial performance, the proportions of indeoendent commissioners influential significant toward financial performance, and the number and size of the company's audit committee not influential significant toward financial performance. Overall result show the good corporate governance in less effect on the performance of the banking syariah companies. Keywords : Good Corporate Governance, Return On Assets (ROA), and financial performance of banking syariah companies.